2011
DOI: 10.1037/a0021048
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the construct network of the Personnel Reaction Blank: Associations with externalizing tendencies and normal personality.

Abstract: Integrity testing has long been utilized in personnel selection to screen for tendencies toward counterproductive workplace behaviors. The construct of externalizing from the psychopathology literature represents a coherent spectrum marked by disinhibitory traits and behaviors. The present study used a sample of male and female undergraduates to examine the construct network of the Personnel Reaction Blank (PRB; Gough, Arvey, & Bradley, 2004), a measure of integrity, in relation to externalizing as well as nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…Secondary analyses that examined the relationship of each of the three NEM primary trait scales to externalizing suggested that the overall NEM association was accounted for primarily by the aggression and alienation components of the construct. Similarly, Blonigen et al (2011) reported that aggression and alienation were among the top three MPQ trait scale predictors of score variance on a 100-item inventory of externalizing symptoms. Together, these results suggest a pervasive role for NEM in conferring vulnerability to psychopathology and should raise questions about conceptualizing this higher-order dimension of personality solely as a vulnerability to disorders of the internalizing spectrum.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Secondary analyses that examined the relationship of each of the three NEM primary trait scales to externalizing suggested that the overall NEM association was accounted for primarily by the aggression and alienation components of the construct. Similarly, Blonigen et al (2011) reported that aggression and alienation were among the top three MPQ trait scale predictors of score variance on a 100-item inventory of externalizing symptoms. Together, these results suggest a pervasive role for NEM in conferring vulnerability to psychopathology and should raise questions about conceptualizing this higher-order dimension of personality solely as a vulnerability to disorders of the internalizing spectrum.…”
Section: Discussionmentioning
confidence: 93%
“…Based on prior research (Patrick, Curtin & Tellegen, 2002; Blonigen et al 2011), we expected that Stress Reaction would show evidence of specificity for Distress and Fear while Aggression would show a comparatively stronger association with Externalizing. To evaluate this, we ran an additional SEM in which these three primary trait scales were each set to predict the three latent psychopathology dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a study that included brain response measures along with questionnaire-based assessment, Hall et al (2007) reported that high overall scores on a 100-item screening form of the ESI were associated with: lower levels of socialization (Gough, 1960); higher and lower scores, respectively, on broad Negative Emotionality and Constraint trait dimensions of the Multidimensional Personality Questionnaire (MPQ; Patrick, Curtin, & Tellegen, 2002; Tellegen & Waller, 2008); higher reported incidence of rule-breaking behaviors in childhood and adulthood; heightened levels of alcohol dependence and drug abuse; and reduced amplitude of the error-related negativity, a brain response that normally occurs following behavioral errors. Relatedly, Blonigen et al (2011) reported that scores on this 100-item ESI strongly predicted scores on a widely-used test of integrity, the Personnel Research Blank (Gough, Arvey, & Bradley, 2004), designed to screen for tendencies toward counterproductive behaviors in employment settings (i.e., higher ESI scores predicted lower integrity scores).…”
Section: Externalizing Spectrum Inventory: Content Structure and Comentioning
confidence: 99%
“…However, the full-form ESI is too long (415 items) for use in extensive protocols (e.g., administrations involving multiple inventories; studies entailing interview, behavioral, and/or physiological assessment along with self-report assessment) or time-limited surveys, and a briefer version is needed as a basis for systematic research on the validity of the ESI measurement model. As an indication of the need for an abbreviated version of the ESI, validation studies to date have relied exclusively on shorter-length forms, designed either to approximate scores on the ESI as whole (Blonigen et al, 2011; Hall, Bernat, & Patrick, 2007; Nelson, Patrick, & Bernat, 2011) or to index its three higher-order factors (Venables & Patrick, 2012). However, the shortened versions used in prior studies do not provide for measurement at the finer-grained, lower-order facet level.…”
mentioning
confidence: 99%
“…Higher overall scores on the ESI were also associated with higher reported incidence of rule-breaking behaviors in childhood and adulthood, and heightened evidence of alcohol dependence and drug abuse. More recently, Blonigen et al (2011) reported that scores on this 100-item version of the ESI strongly predicted scores on a well-established integrity test, the Personnel Research Blank (Gough, Arvey, & Bradley, 2004), designed to screen for tendencies toward counterproductive behaviors in employment settings (i.e., higher ESI scores predicted lower integrity scores). These results provide additional evidence for the validity of scores on the ESI as a whole.…”
Section: Externalizing Spectrum Model: Conceptualization and Measurementmentioning
confidence: 99%